Sharing economy and the impact of collaborative consumption - Luna, Iviane Ramos de, 1964-; Fitó Bertran, Àngels; Lladós Masllorens, Josep (Advances in finance, accounting, and economics (AFAE) book series., 2020)
"This book examines the impact of sharing services on society as well as the importance of the sharing economy development in the coming years. It also explores issues related to these sharing services such as regulations, the technological aspects involved in these platforms, and the impact on the tourism sector and consumer behavior"--